Evaluating soil metallic pollution and consequent human health hazards in the vicinity of an industrialized zone, case study of Mubarakeh steel complex, Iran. Issue 1 (December 2015) - Ghaemi, Zohreh; Karbassi, Abdolreza; Moattar, Faramarz; Hassani, Amirhesam; Khorasani, Nematollah
Abstract Background Being established in 1988 in the vicinity of Isfahan city, Mubarakeh Steel complex has imposed adverse environmental and health effects within the area. The study area is covered by lots of farms through which major crops like wheat and rice are provided. Methods Considering the imposed pollution load of the complex, the current study has monitored the concentration of metals Fe, Al, Cd, Cr, Ni, Pb, Cu, Zn, Mn, Co, Mo, As in 14 soil samples within the study area. Furthermore, human health hazards of mentioned metals due to consumption of domestic rice and wheat have also been evaluated through different scenarios. In order to evaluate the mobility of metals in soil samples the sequential chemical analysis is performed. Results Regarding the accumulation of metals in loose phases the order of metals bioavailability risk level is estimated to be as follows: Co > Cd > Mo > Ba > As > Pb > Mn > Cu > V > Zn > Cr > Ni Discussion An index approach is also considered to evaluate the severity of metal contamination. Regarding geochemical accumulation index, only cadmium is detected to be in a moderately contaminated status while other metals declare an unpolluted condition. Index of pollution pays more attention to mobility potential of metals and accordingly detects metals Co, Mn, As, Pb, Cd, Ba and Mo to be in a moderately contaminated level. On the other hand, enrichment factor declares all toxic metals except for Co, Ba and V to be enriched. Conclusions Considering human health hazard assessment, except for Fe, Ba, Cu and Zn, all metals intakes in different scenarios are considered as hazardous while their CDI values are much more than the respective oral reference doses.